Biologia reprodutiva e seleção dos sítios de nidificação de Emberizoides ypiranganus (aves: passeriformes) em campos de altitude no sul do Brasil - Chiarani, Eduardo (2014)
We studied the breeding biology of the Lesser Grass-finch (Emberizoides ypiranganus), a bird little known regarding your life history, in upland grassland of Mata Atlântica Biome in southern Brazil. We collected data over two breeding seasons (from October to March of 2012-2013 and 2013-2014) in the Parque Estadual do Tainhas (29º 5 58 S, 50° 21 50 W), in northeastern of Rio Grande do Sul State, Brazil. We monitored 93 nests and assessed several aspects related to reproduction of the species such as territoriality, breeding chronology, characteristics of nests, eggs and nestlings, clutch size, incubation, hatching rate, parental care, reproductive success and habitat features (structure and floristic composition) important in the nest site selection. Breeding begins at the first week of October, peaks in late November, and lasts until early March. The average size of reproductive territories was 1.1 ± 0.5 ha. Burned areas had smaller territories and a smaller density of reproductive pairs in comparison with unburned areas. Nests were built in transition zones between dry and wet habitats (49.5%) or in dry grasslands (48.4%). Only 2.1% of nests were built in dense marshes. The structure and floristic composition of nest sites analysis showed that the species selects sites to build nests with higher abundance of grass clumps such as Andropogon lateralis, Schizachyrium tenerum e Sorghastrum setosum. Nests are cup-shape and are built only by female in 3-7 days, at 36.2 ± 11.6 cm above the ground. The clutch size is three (67.3%) or two eggs. The incubation, which is performed by the female, lasts 13 to 14 days and is synchronic. The hatching rate was 93.5%. Nestlings remain in the nest between nine and 12 days. In most nests the nestlings are feed by both male and female (biparental care). The frequency visits to the nest to feed young did not differ with the nestling ages, but the length of visits was longer when nestlings were one to five days old. The apparent nest success was 41.9%, while the Mayfield success was 39.3% and MARK 35%. Predation was the main cause of loss clutches, affecting 76% of the unsuccessful nests. The best model to nest survival includes time-specific factors (nest age and year) and nest site features (nest height and habitat). The daily survival rates decrease through the nest cycle, falling sharply after hatch, on nestling stage. In successful nests the nestling survival was 0.83 ± 0.24 and the average productivity 2 ± 0.76 fledglings/nests. Considering successful and unsuccessful nests, the productivity was 0.84 ± 1.11 fledgling/nests. Up to four nest attempts, performed by the same female, were observed in a breeding season. The renesting interval after nest failure was 2.7 ± 1.3 days and the average distance among consecutive attempts was 104.2 ± 60.2 m. Although there is few available information in literature about the reproduction of Lesser Grass-finch, some basic parameters found are similar to those described. However, many results of this study are unpublished for the species such as territoriality, reproductive success and nest site selection.